Bone matters in lung cancer - Brodowicz, Thomas; O'Byrne, Ken; Manegold, Christian (Annals of oncology, 2012)
Background: Bone metastases are a signiﬁcant and undertreated clinical problem in patients with advanced lung cancer. Design: We reviewed the incidence of bone metastases and skeletal-related events (SREs) in patients with lung cancer and examined the burden on patients’ lives and on health care systems. Available therapies to improve survival and lessen the impact of SREs on quality of life (QoL) were also investigated. Results: Bone metastases are common in lung cancer; however, owing to short survival times, data on the incidences of SREs are limited. As with other cancers, the costs associated with treating SREs in lung cancer are substantial. Bisphosphonates reduce the frequency of SREs and improve measures of pain and QoL in patients with lung cancer; however, nephrotoxicity is a common complication of therapy. Denosumab, a recently approved bone-targeted therapy, is superior to zoledronic acid in increasing the time to ﬁrst on-study SRE in patients with solid tumours, including lung cancer. Additional roles of bone-targeted therapies beyond the prevention of SREs are under investigation. Conclusions: With increasing awareness of the consequences of SREs, bone-targeted therapies may play a greater role in the management of patients with lung cancer, with the aim of delaying disease progression and preserving QoL.
Gesehen am 22.10.2018